PENGEMBANGAN BAHAN AJAR BERBASIS PENDEKATAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA SMA DHARMAWANGSA MEDAN - Umaysy Sabillah; Hasratuddin Hasratuddin (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This study aims to obtain teaching materials based on a valid, practical, and effective realistic mathematical approach, so as to improve students' mathematical reasoning abilities on the material of a three-variable linear equation system. The research instruments used were questionnaire validation sheets, lesson plans validation sheets, teaching material validation sheets, test instrument validation sheets, mathematical reasoning ability tests, and teacher and student response questionnaires to teaching materials. After all instruments, lesson plans, and teaching materials were declared valid by the validator, then readability tests and field trials were carried out. The results showed that: (1) the teaching materials based on the realistic mathematical approach developed had met the criteria of validity based on the validator's assessment with the average validity of the teaching materials for the material being 3.13 and 3.29 for media with a very feasible category; (2) the teaching materials based on the realistic mathematical approach that have been developed have met the practicality criteria through: a) the results of the questionnaire student responses to teaching materials show the percentage of practicality of 81.19% with a very practical category, b) the results of the questionnaire responses of teachers to teaching materials show the percentage of practicality 88.75% with very practical category; (3) The teaching materials based on the realistic mathematics approach developed meet the effective criteria with: a) classical student learning mastery of 88%, b) more than 65% of students have achieved 75% of learning objectives for each indicator, c) increased mathematical reasoning ability students after using teaching materials seen through the average score of students increased from 50 in the pretest to 85.33 in the posttest and the results of the N-Gain analysis which showed students' mathematical problem solving abilities increased by 0.712, meaning in the high category.